Pengaruh Media Sosial,Citra Merek Dan Kualitas Produk Terhadap Keputusan Pembelian Mahasiswa Unisma Di Clodia Outfit Malang (Studi Kasus Pada Mahasiswa Unisma Malang) - Vicky Dwi Anggraeni; Rois Arifin; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This pandemic phenomenon makes it a challenge for business actors to maintain income and economic growth, one of which is Clodia Outfit in running their business. During the COVID-19 pandemic, employees remain at home, but in this case it doesn't make Clodia Outfit not run its business. The purpose of this study is to simultaneously analyze the influence of social media, brand image and product quality on purchasing decisions of UNISMA students at Clodia Outfit Malang. This research design uses a quantitative approach with descriptive data analysis conducted in November 2021. The sample used is a purposive sampling technique. Multiple linear regression test resulted that there was an influence between social media on purchasing decisions (sig. = 0.000). There is an influence between brand image on purchasing decisions (sig = 0.000). There is an influence between product quality on purchasing decisions (sig = 0.000). The conclusion of this study is that social media, brand image and product quality have a simultaneous and significant effect on purchasing decisions for UNISMA students at Clodia Outfit Malang. Clodia Outfit must continue to provide consistent prices so that it can increase sales, continue to serve well, create or make something different from the others that can attract the attention of consumers, and still maintain the quality of its products. Keyword :  Social Media, Brand Image, Product Quality and Purchase  Decision